(untitled) (Portuguese Journal of Family Medicine and General Practice, 2008)
Alcohol Related Problems are very important because they are the cause of many different physical, psychological and social conditions. Preventing the damage of alcohol related problems is a process involving many actors in society. To inform the population of those consequences are also primary health care professionals responsibility. In this text the authors classified prevention and consider its importance when concerning to alcohol related problems in primary health care; they justify also the reason of doing screening of these problems among the patients in PHC and how to promote an healthier life style among this population.